2013
DOI: 10.1007/s11845-013-0955-5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards patients with mental illness in Irish medical students

Abstract: Given the high rates of physical illness in patients with mental health problems, specific educational initiatives to address medical student's attitudes to patients with mental health problems should be an educational priority in medical school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Portuguese medical students have similar results to some studies that showed good or better attitudes towards the psychiatric patients in late medicine school years, 23 after psychoeducation [24][25][26][27][28][29] and psychiatric teaching. [30][31][32] Although our students' attitudes showed a regression in scores after the third year, they were still better at the end of the course than the in first year.…”
Section: Discussionsupporting
confidence: 70%
“…Portuguese medical students have similar results to some studies that showed good or better attitudes towards the psychiatric patients in late medicine school years, 23 after psychoeducation [24][25][26][27][28][29] and psychiatric teaching. [30][31][32] Although our students' attitudes showed a regression in scores after the third year, they were still better at the end of the course than the in first year.…”
Section: Discussionsupporting
confidence: 70%
“…In particular, medical students acknowledge the value of psychotherapy ( 21 ), view psychiatry as intellectually challenging and personally rewarding, but are reported to entertain a certain skepticism toward factors such as scientific standing, status, prestige and financial prospects, psychiatrists, patients, and treatment ( 18 ). In previous studies, female medical students and those with previous experience with psychiatry had consistently more positive attitudes ( 18 , 20 , 21 , 23 , 24 , 28 , 29 ), higher general interest in psychiatry ( 18 ), or higher interest in psychiatry as a career ( 20 , 22 , 25 28 ). Attitudes toward psychiatry and the definite career choice might also depend on characteristics of the medical school concerned, such as selection of students by non-teachable competencies, cultural diversity among medical students or the medical school’s focus on psychiatric education, and the supportiveness of the faculty ( 18 , 20 ).…”
Section: Introductionmentioning
confidence: 78%
“…In order to learn more about medical students’ views of psychiatry, numerous studies have focused on their attitudes toward psychiatry and their intended or definite career choice in order to obtain a deeper insight into the factors which might contribute to a better standing ( 18 29 ). Most studies indicate a discrepancy between positive attitudes toward psychiatry and low willingness to work in the field ( 18 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings about the positive impact of the psychiatry clerkship were in parallel with previous study findings. [5][6][7][8] Learning based on experience with real patients is essential in clinical education. However, the experience is not competent enough alone, and should be reconstructed by reflective practices over interactions with the trainee him/herself, other people, opinions and other components of the environments.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Reducing stigmatization of mental illness of medical students is an important aim of medical education. Findings show that the educational programs implemented in this regard either improve the stigmatization attitudes of students [5][6][7][8] or do not have any impact [9][10][11] or do not contribute to being ready to provide medical care to such patients. 12 Educational approaches like lecture, 13 webbased program, 14 watching videotaped, 15 humanizing approach, 16 peer sharing of personal experince, 17 experience of simulated auditory hallucinations 18 and contact-based sessions 19 are effective in reducing mental illness stigmatization among medical students.…”
Section: Introductionmentioning
confidence: 94%